2010
DOI: 10.1590/s1679-87592010000500004
|View full text |Cite
|
Sign up to set email alerts
|

Paleoproductivity changes during the Late Quaternary in the southeastern Brazilian upper continental margin of the Southwestern Atlantic

Abstract: A B S T R A C TChanges in the Brazilian continental margin's oceanic productivity and circulation over the last 27,000 years were reconstructed based on sedimentological and microfaunal analyses. Our results suggest that oceanic paleoproductivity and the supply of terrigenous sediments to the Brazilian continental margin were higher during the Last Glacial Maximum (LGM) than during the Holocene. These changes may have been primarily influenced by significant sea level fluctuations that have occurred since the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 35 publications
(58 reference statements)
2
22
0
5
Order By: Relevance
“…The decrease in productivity during the Holocene can be attributed to a progressive strengthening of the BC as a result of the southward displacement of the Intertropical Convergence Zone caused by changes in insolation related to the precessional cycle (Toledo et al 2008). Nagai et al (2010) studied the foraminiferal signatures of a sediment core collected from the same region as that of the present study, and also reported increased benthic productivity during MIS 2. Those authors proposed that the presence of species considered to be indicative of high food availability (Bulimina marginata and Uvigerina peregrina) reflected a higher input of organic matter.…”
Section: Marine Productivitymentioning
confidence: 57%
See 1 more Smart Citation
“…The decrease in productivity during the Holocene can be attributed to a progressive strengthening of the BC as a result of the southward displacement of the Intertropical Convergence Zone caused by changes in insolation related to the precessional cycle (Toledo et al 2008). Nagai et al (2010) studied the foraminiferal signatures of a sediment core collected from the same region as that of the present study, and also reported increased benthic productivity during MIS 2. Those authors proposed that the presence of species considered to be indicative of high food availability (Bulimina marginata and Uvigerina peregrina) reflected a higher input of organic matter.…”
Section: Marine Productivitymentioning
confidence: 57%
“…This has confirmed the important role of major reorganization of Atlantic thermohaline circulation in abrupt climate change (Mahiques et al 2005(Mahiques et al , 2007Toledo et al 2007aToledo et al , 2008Nagai et al 2010;Pivel et al 2010Pivel et al , 2013Leonhardt et al 2013;Mendoza et al 2014;Chapori et al 2015). For the southwestern Atlantic, study of planktonic foraminiferal records has suggested that productivity was higher during deglaciation than in the last glacial maximum (LGM) and the Holocene (Toledo et al 2007b), although other studies have shown that productivity peaked during the LGM and the Younger Dryas in the same region (Mahiques et al 2007;Toledo et al 2008).…”
Section: Introductionmentioning
confidence: 67%
“…Hydrodynamic changes in the Brazilian continental margin, derived from sea-level fluctuations, have been explored previously (Mahiques et al 2007;Nagai et al 2010). According to these authors, low sea-level conditions promote offshore displacement of the BC, resulting in a less intense action of this current on the shelf.…”
Section: Holocene Palaeo-oceanographic Evolutionmentioning
confidence: 99%
“…Only a few studies investigated changes in paleoproductivity in the oligothrophic 305 western South Atlantic Ocean (i.e., Mahiques et al, 2007;Nagai et al, 2010;Toledo, 2008;306 Toledo et al, 2007). Toledo (2008) …”
mentioning
confidence: 99%
“…Mahiques et al (2007) and Nagai et al (2010) found increased 310 productivity during the Last Glacial Maximum (LGM, 23 to 19 ka, and 311 relatively stable paleoproductivity values during Termination 1. Even during the LGM our 312…”
mentioning
confidence: 99%